The Medium Shapes the Message: McLuhan and Grice Revisited in Race Talk Online - August, Caren; Liu, James H. (Journal of community & applied social psychology, 2015)
Compared with the wealth of research accumulated on face‐to‐face social interactions, relatively little research has examined race talk within anonymous Web 2.0 mediums. We investigated online threaded comments on YouTube video clips of two race‐related incidents involving New Zealand television presenter Paul Henry. Through thematic content analysis, thematic analysis, and discourse analysis, it was found that characteristics unique to Web 2.0 were associated with the appearance of old‐fashioned racism and high‐levels of obscenity (together with modern racism/symbolic racism). The hyper‐low context of communication led to interpretive ambiguity; conversation sequences failed to follow Gricean maxims for cooperative communication, with most comments attracting no replies and the modal sequence being two turns. There was almost never resolution to a disagreement online: rather there was points‐scoring against opposing opinions and a tangential style of dialogue influenced by the asynchronous and anonymous nature of communication. The YouTube medium shaped but did not determine the message, as obscenity and racist content in the target video from the eliciting public figure influenced the subsequent degree of obscenity and hostility in the responses. A third corpus that examined responses to our own research on race talk presented on a news website (stuff.co.nz) underlined this point by engendering a dramatically different response to the same subject, retaining the tangential style of communication, but with little to no obscenity. A framework to understand race talk as a function of both medium and context effects is proposed. Copyright © 2014 John Wiley & Sons, Ltd.